PENENTUAN BIAYA PRODUKSI UNTUK MENGHITUNG JASA PADA UMKM AULIA LAUNDRY - Milania, Lia; Kartika, Tia; Adira Putri, Dea; Alvionita Agustin, Wanda (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
Micro, Small and Medium Enterprises (MSMEs) Aulia Laundry is a business unit engaged in services carried out by small communities in the Kubang Raya area, Tambang District, Pekanbaru City. Based on direct observations on UMKM Aulia Laundry, it is known that transaction data management has not used a computerized system, such as recording customer data, transaction data, and making delivery notes which are still done manually where every activity is still stored in the ledger. This is of course impractical, because the data storage system is still in the form of archiving so that archive accumulation often occurs which can make data security less guaranteed.With the many shortcomings that exist in these SMEs, this research is needed with the aim of knowing the production costs of Aulia Laundry SMEs, so that they can determine the cost of production. Usually in business production activities require the sacrifice of economic resources in the form of various types of costs to produce products to be marketed. These costs are the basis for determining the Cost Of Production (HPP). This is intended to make it easier for MSME entrepreneurs to know the costs incurred to produce a product and avoid mistakes in determining the selling price.